2022
DOI: 10.1155/2022/5227335
|View full text |Cite
|
Sign up to set email alerts
|

Isoschaftoside Inhibits Lipopolysaccharide-Induced Inflammation in Microglia through Regulation of HIF-1α-Mediated Metabolic Reprogramming

Abstract: Isoschaftoside is a C-glycosyl flavonoid extracted from the root exudates of Desmodium uncinatum and Abrus cantoniensis. Previous studies suggested that C-glycosyl flavonoid has neuroprotective effects with the property of reducing oxidative stress and inflammatory markers. Microglia are key cellular mediators of neuroinflammation in the central nervous system. The aim of this study was to investigate the effect of isoschaftoside on lipopolysaccharide-induced activation of BV-2 microglial cells. The BV-2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Kaempferitrin has effects that inhibit cell proliferation, promote cell apoptosis, and ameliorate inflammation . Isoschaftoside has neuroprotective effects by reducing oxidative stress and inflammatory markers . In kidney bean, quercetin5-O-glucuronide and quercetin-3-O-sambubioside were more abundant than in other legumes and cynaroside and astragalin were specifically contained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaempferitrin has effects that inhibit cell proliferation, promote cell apoptosis, and ameliorate inflammation . Isoschaftoside has neuroprotective effects by reducing oxidative stress and inflammatory markers . In kidney bean, quercetin5-O-glucuronide and quercetin-3-O-sambubioside were more abundant than in other legumes and cynaroside and astragalin were specifically contained.…”
Section: Resultsmentioning
confidence: 99%
“…36 Isoschaftoside has neuroprotective effects by reducing oxidative stress and inflammatory markers. 37 In kidney bean, quercetin5-O-glucuronide and quercetin-3-O-sambubioside were more abundant than in other legumes and cynaroside and astragalin were specifically contained. Cynaroside possesses antibacterial, antifungal, antileishmanial, hepatoprotective, antidiabetic, and anticancer properties.…”
Section: Flavonoid Profiles Of Five Fresh Legumes Detected Bymentioning
confidence: 94%
“…Among the many beneficial flavonoids, one can underline the anti-inflamma-tory action of isoschaftoside found in E. alata, for example [95]. This compound is a potent antioxidant and an anti-inflammatory agent with an anti-steatosis activity useful to combat metabolic liver disease [165,166]. Other flavonol glycosides, such as isorhamnetin-3-O-rutinoside, contribute similarly to the antioxidant and anti-inflammatory effects [16].…”
Section: Discussionmentioning
confidence: 99%
“…21 Notably, HIF-1α accumulates in all proinflammatory activated immune cells, including macrophages, under normoxic conditions and is involved in regulating the transcription of inflammatory genes such as Il-1β. [22][23][24] HIF-1α inhibition markedly reduces Il-1β gene expression, and myeloidspecific HIF-1α deletion protects against inflammationinduced acute and chronic liver injury. 25,26 A small number of studies have indicated a protective role of HIF-1α inhibitors against inflammation-induced acute liver failure, 25,27 but this effect has not yet been well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Under normoxic and homeostatic conditions, HIF‐1α protein is prolyl‐hydroxylated by prolyl hydroxylases (PHDs) and subsequently polyubiquitinated by von Hippel–Lindau tumor suppressor protein (VHL), marking it for proteasomal degradation 21 . Notably, HIF‐1α accumulates in all proinflammatory activated immune cells, including macrophages, under normoxic conditions and is involved in regulating the transcription of inflammatory genes such as Il‐1β 22–24 . HIF‐1α inhibition markedly reduces Il‐1β gene expression, and myeloid‐specific HIF‐1α deletion protects against inflammation‐induced acute and chronic liver injury 25,26 .…”
Section: Introductionmentioning
confidence: 99%